2012
DOI: 10.1038/cr.2012.48
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of the CUL4B ubiquitin ligase in extra-embryonic tissue development during mouse embryogenesis

Abstract: Mutations of the CUL4B ubiquitin ligase gene are causally linked to syndromic X-linked mental retardation (XLMR). However, the pathogenic role of CUL4B mutations in neuronal and developmental defects is not understood. We have generated mice with targeted disruption of Cul4b, and observed embryonic lethality with pronounced growth inhibition and increased apoptosis in extra-embryonic tissues. Cul4b, but not its paralog Cul4a, is expressed at high levels in extra-embryonic tissues post implantation. Silencing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 39 publications
1
67
0
Order By: Relevance
“…Mice-Generation of conditional Cul4b mice was described previously (7). The Vasa(Ddx4)-Cre (stock no.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice-Generation of conditional Cul4b mice was described previously (7). The Vasa(Ddx4)-Cre (stock no.…”
Section: Methodsmentioning
confidence: 99%
“…Here we investigate the role of Cul4b in murine spermatogenesis. Our previous studies showed that Cul4b mutant mouse embryos died in midgestation because of a G 2 /M arrest in extraembryonic tissues, whereas epiblast-specific null mutants survived to adulthood with no overt developmental defects (7). To investigate the role of CUL4B protein in mammalian spermatogenesis, we generated and characterized germ cell-specific as well as global Cul4b mutant mice.…”
mentioning
confidence: 99%
“…CUL4A, CUL4B, and Cdt2 Knockdown Cell Lines-Human CUL4A, CUL4B shRNA, and control shRNA were as described previously (47,48). Human Cdt2-shRNA (mature sense sequence, GGTTATCAGTGCAGTGGT) was obtained from Open Biosystems.…”
Section: Methodsmentioning
confidence: 99%
“…Examples of where one or the other CUL4 genes exhibit predominant roles are in the regulation of DDB2 and p21 in mouse epithelial cells by CUL4A, and in mouse models where CUL4A is essential for spermatogenesis and male fertility (59). Deficiency of CUL4B is associated with syndromic X-linked mental retardation in humans (60), and mice with targeted disruption of CUL4B show that it has an essential role in extra-embryonic tissue development during embryogenesis (48).…”
Section: Cdt2mentioning
confidence: 99%
“…In the most recent study published in Cell Research, Zhou and coworkers [12] attempted to generate conditional Cul4b knockout mice with targeted deletion of Cul4b at exons 4 and 5, giving rise to a non-functional Cul4b fragment lacking both the DDB1-binding domain and the cullin homology domain for RBX1 recruitment. The chicken-actin (CAG)-Cre was used, which drives Cre-mediated recombination at the early zygote stage, leading to Cul4b deletion in both the embryo proper and extraembryonic tissues.…”
mentioning
confidence: 99%